Revisiting Earnings Persistence: A Global Bibliometric Analysis of its Intellectual and Citation Structure - Loso Judijanto (Eastasouth Institute, 2026)
This study re-explores the literature on earnings persistence by adopting a global bibliometric approach to mapping its intellectual foundations, thematic evolution, and citation structure. Using publication data indexed in Scopus, this study applies citation analysis, co-authorship analysis, and science mapping techniques-including keyword co-occurrence, overlay, and density visualizations-generated via VOSviewer. The findings indicate that earnings persistence research is anchored around a core set of influential works and concepts, with earnings, income, and employment as central themes. Over time, the literature has evolved from an initial focus on labor market structures and human capital toward more recent emphases on wage dynamics, returns to education, and issues of discrimination and inequality. Collaboration patterns indicate the dominance of developed countries, particularly the United States, alongside emerging but still fragmented international research networks. This study systematically synthesizes several decades of scholarly output and as such clarifies the intellectual and conceptual structure of earnings persistence research, while pointing to promising directions for future inquiry. The results add to a deeper understanding of how earnings persistence has developed as a mature and interdisciplinary field spanning accounting, finance, and labor economics.